Eleven years' experience with Intrathecal Baclofen – Complications, risk factors. Issue 5 (30th March 2018) - Pucks‐Faes, Elke; Hitzenberger, Gabriel; Matzak, Heinrich; Fava, Elena; Verrienti, Giulio; Laimer, Ilse; Fritz, Josef; Saltuari, Leopold
Abstract: Objective: Treatment with intrathecal baclofen (ITB) is commonly used in patients with severe spasticity. However, complications may occur after implantation of the ITB‐device, albeit mainly procedure‐ and device‐related problems. The aim of the study was to assess surgical‐ as well as catheter‐ and pump‐related complications and define their risk factors. Methods: We retrospectively evaluated all patients with an implanted ITB‐device who were treated at the Department of Neurology, Hochzirl Hospital, Zirl, Austria, between 2006 and 2016. Results: Twenty‐nine of 116 (25%) patients experienced 32 complications: 5 procedure‐ and 27 device‐related (4 pump‐ and 23 catheter‐associated) problems occurred. Risk factors for sustaining any complication were a spinal localization of lesion (odds ratio [OR] OR 2.71, p  = .021), other catheter types than an Ascenda ® catheter (OR 3.87, p  = .041), a lower modified Rankin Scale (median 4 vs. 5; OR 2.86, p  = .015) and a higher Barthel Index (median 53 vs. 0; OR 2.84, p  = .006). The median time from the last ITB‐related surgery to the first complication was 18 (IQR 1‐57) months. Overall, 47% complications occurred within the first year after any surgical procedure regarding the ITB‐device, thereof 25% within the first month. Conclusions: Procedure‐ and device‐related complications are frequent after implantation of an ITB‐device with catheter‐associated complications as the most frequently encountered problems. Patients with a spinal origin of spasticity, a lower modified Rankin Scale and a higher Barthel Index have a higher risk to sustain a complication. Abstract : In this study we retrospectively investigated complictaion rates and their risk factors in long term ITB therapy. Highest occurence of complications were found in the first year after implantation and was associated with spinal origin of spasticity, a higher degree of independence in ADLs and catheter types other than an Ascenda ® catheter.